SIMPENDI-PHB: Sistem Informasi Manajemen Pengelolaan Penelitian dan Pengabdian Masyarakat Berbasis Website - Ginanjar Wiro Sasmito; M Fikri Hidayatullah; Fina Yuniarti; Riszki Wijayatun Pratiwi; Sharfina Febbi Handayani; Dairoh; Ratono; Dwi Intan Af’idah (Infotekmesin, 2022)
Document management for submission of proposals, assessments, and reports on research and service activities at the Research and Community Service Center of the Harapan Bersama Polytechnic is still manually carried out and not computerized. To facilitate the process of implementing, managing research and service management as well as supervising research, service, publication, and evaluation activities, an information system was built using the waterfall method. This system has been created under the name SIMPENDI PHB by involving 9 actors. The result is that the system runs according to the functions of the actors involved. This system was tested with black box and usability. The results of system testing (black box) is that 9 actors involved in this system have been running according to the function of each actor. As for the usability results by involving several actor menus, namely as many as 30 users consisting of 6 managers in related units, 4 users from the assessment team, and the proposer users (lecturers) is a UI/UX score of 86% in the "Very good" category.